Experimental determinations of the horizontal mixing coefficients along the Romanian west coast of the Black Sea - Popa, Adriana; Diaconu, Vasile (Cercetări Marine - Recherches Marines, 2026)
The space-scale dependence of the turbulent mixing coefficients as determined from turbulent diffusion of dissolved substances, dispersion of finite particles and current velocity fluctuations during 1976-1980 is presented, and the deviations from the "4/3 power law" in the shallow waters are pointed out.